Management Of Collaborative Development Of Chinatown Village As A Tourist Attraction In Cirebon City - Ningsih, Widia; Suryono, Chondro (Jurnal Toursci, 2024)
Chinatown is one of the alternative tourist destinations for tourists because it is not only part of history but is the heart of Cirebon. With the development of Chinatown villages, the community can be more proud and appreciate the value of local history and culture. In terms of Collaborative Management of Chinatown Development, which involves various essential components, including the government, the private sector, academics, and the community, trying to develop the potential possessed by Chinatowns, in addition to the great potential owned, several things are obstacles in the development of Chinatowns, including the low quality of human resources who fully understand sustainable management. This research activity is a field study using research methods by conducting observations and interviews with the government, the private sector, academics, and the community in the Kanoman Palace regarding the Collaborative Management of Chinatown Development as a Tourist Attraction in Cirebon City. Collaborative Management of Chinatown Development as a Tourist Attraction in Cirebon City is one of the Cirebon City Tourism Attractions which in the future will be managed well by various parties, both from the government, local communities, and the community on a sustainable basis (Sustainable management).